Determination of critical point of p02 L]level in the production of lactic acid by Lactobacillus rhamnosus - Mel, Maizirwan; Abdulkarim, Mohd Ismail; Mohamed Salleh, Mohamad Ramlan; Abdullah, Rohane (Asian Network for Scientific Information, 2007)
The study was conducted to determine the critical point of p02 level in the production of lactic acid by Lactobacillus rhamnosus. The fermentation process was successfully carried out in laboratory scale fermenteribioreactor using different p02 level (the main parameter that significantly affects the growth of L. rhamnosus and lactic acid production) together with two other parameters; the agitation rate and pH. From the result, it was observed that the best production of lactic acid with the concentration of 16.85 g L -1 or 1.68% production yield has been obtained at the operating parameters of 5% p02 level, agitation speed of 1 00 rpm and sample pH 6. The critical point of p02 was fOlUld to be between 5 and 10%.